Impact of Wordwall Based Joyful Learning on Science Learning Achievement - Nurfatiah Pakaya; Achmad Ramadhan; Yuniasih Yuniasih (Equator Science Journal, 2025)
This study aims to improve student learning outcomes in Biology through the application of the Joyful Learning approach supported by Wordwall interactive media. The method used in this study was Classroom Action Research (CAR) conducted in two cycles and involving 34 students of class XI SMA Negeri 2 Palu as research subjects. Each cycle of this study included the stages of planning, implementation, observation, and reflection. Data were obtained through observation sheets and learning outcome tests, then analyzed descriptively by considering the average score and percentage of classical mastery. The results showed that in the pre-cycle stage, student learning mastery only reached 41.18% with an average score of 70.00. After the action in cycle I was implemented, mastery increased to 67.65% with an average score of 76.35. A further improvement in cycle II resulted in a significant increase, namely 88.24% mastery with an average of 81.56. Thus, the application of the Wordwall-based Happy Learning approach proved to be effective in creating a conducive learning atmosphere, increasing student participation, and encouraging more optimal understanding of the material.